Impact of adenotonsillectomy on hearing profile of children with chronic middle ear effusion - James, Febin; George, Josmy; M., Regina (International Journal of Contemporary Pediatrics, 2018)
Background: Chronic middle ear effusion (CME) also known as otitis media with effusion (OME)/glue ear/secretory otitis media is the commonest cause of hearing loss in children, characterized by presence of sterile serous fluid within the middle ear, causing temporary and reversible hearing loss. The aim of present investigation was to determine the effect of adenotonsillectomy on hearing profile of children with persistent OME. Methods: This prospective study was conducted in the Department of ENT, Aarupadai Veedu Medical College, Pondicherry during the period of June 2014 to February 2016. 50 children, between the age group of 3-12 years, with features suggestive of OME, and adenotonsillar hypertrophy that underwent adenotonsillectomy during the study period was included in this study. Demographic details and clinical features were collected from the participants. Hearing evaluation was performed by pure tone audiometry (PTA) and tympanometry preoperatively at time of diagnosis and postoperatively at 6 weeks and 3 months after adenotonsillectomy. Data collected was plotted into master chart and analysed using paired t-test and chi square test to determine the improvement in hearing after 6 weeks and 3 months following surgery. Results: 46 children aged between 3 and 12 years with a mean age of 5.3 and standard deviation of 2.2 years. OME was most prevalent in age group was 5-7 years (34.78%) followed by 7-9 years (30.43%). There were 26 (56.52%) males and 20 (43.47%) females. Pre-operatively most of the subjects were having moderate conductive hearing loss (between 26dB to 40dB) with a mean hearing loss of 34.2dB and a standard deviation of 12.2dB. At 6 weeks postoperatively, hearing loss of children were within 16-25dB with a mean loss of 21.6dB and a standard deviation of 6.4dB. At 3 months postoperatively, 30 children were having only minimal hearing loss and 8 were having mild hearing loss. Conclusions: CME is a common cause of childhood hearing loss having a long-term sequel affecting the language development of the child. Adenoidectomy can improve the middle ear function and the hearing profile of child and can be considered as a practical management option in children with chronic adenotonsillar hypertrophy with established otitis media with effusion.